Reliability and Validity of the 90º Push-Ups Test Protocol (International Journal of Scientific Research and Management (IJSRM), 2018)
- This study was conducted to determine the objectivity, reliability and validity of the 90º push-ups test protocol among male and female students of Sports Science Program, Faculty of Sports Science and Coaching Sultan Idris University of Education. Samples (n = 300), consisted of males (n = 168) and females (n = 132) students were randomly selected for this study. Researchers tested the 90º push-ups on the sample twice in a single trial, test and re-test protocol in the bench press test. Pearson-Product Moment Correlation method’s was used to determine the value of objectivity, reliability and validity testing. The findings showed that the 900 push-ups test protocol showed high consistency between the two testers with a value of r = .99. Likewise, The reliability value between test and re-test for the 90º push-ups test for the male (r=.93) and female (r=.93) students was also high. The results showed a correlation between 90º push-ups test and bench press test for boys was r = .64 and girls was r = .28. This finding indicates that the use of the 90º push-ups to test muscular strength and endurance in the upper body of males has a higher validity values than female students.